PERIPHERAL NEUROPATHY ASSOCIATED WITH WHIPPLE'S DISEASE. Issue 12 (15th November 2016) - Kumar, Guru; Mohamed, Mohamed; Redmond, Ian; Harikrishnan, Sreedharan
Abstract : Whipple's Disease (WD) is a chronic multisystem infectious disease caused by the bacterium Tropheryma Whipplei. Neurological manifestations typically involve cognitive impairment and deranged ocular movement with ophthalmoplegia or oculomasticatory myorhythmia. A fifty-five year old Caucasian presented with visual disturbance, patchy lower limb weakness and dysthesia with intermittent abdominal pain and weight loss progressing over several months. He was diagnosed with bilateral uveitis and an axonal motor sensory peripheral neuropathy confirmed with neurophysiology. Blood tests for common metabolic, inflammatory and infectious causes were non diagnostic and routine constituents of cerebrospinal fluid (CSF) were normal. Imaging of the neural axis was normal. Visual symptoms improved with oral steroids however his weakness deteriorated. Abdominal imaging demonstrated jejunal thickening; histology of which yielded macrophages positively stained with Periodic Acid-Schiff (PAS). DNA of Tropheryma Whipplei was detected in this bowel lesion and concurrent serum, however CSF was negative. There was improvement of symptoms with commencement of antimicrobial treatment, thus it was felt nerve biopsy was not indicated. Peripheral nerve involvement in WD is believed to be uncommon and we present an unusual manifestation of disease. This case highlights the need to consider rare diagnoses of peripheral neuropathy when associated with multisystemic symptoms with no attributable cause.